Quality of Life Following Surgical and Conservative Therapy of Pyogenic Spinal Infection: A Study of Long-term Outcome in 210 Patients - Behmanesh, Bedjan; Gessler, Florian; Duetzmann, Stephan; Seifert, Volker; Weise, Lutz; Setzer, Matthias (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Object The management and recommendations for treatment strategies of pyogenic spinal infection are still a highly controversial issue. The purpose of this study was to evaluate patient's quality of life (QoL) after surgical and conservative treatment of spinal infection.Materials and Methods We conducted a retrospective, single-center study. All patients treated between 2009 and 2016 were included in this study. For evaluation of QoL, we recorded each patient's satisfaction according to the 36-Item Short Form Health Survey (SF-36) questionnaire. Scores were compared with a U.S. standard population.Results Two hundred and ten adult patients with spondylodiskitis were identified. Of these, 155 (74%) underwent surgery and 55 (26%) were treated conservatively. The mean overall age was 68.6 (23–98) years. Seventy-two patients were females and 138 patients were males. The mean outcome values in the surgical group did not reach the level of the normative sample in one of eight items, whereas the conservative group revealed a reduced QoL in all items. Intergroup comparison revealed significant differences in all items (p < 0.05).Conclusion In the patient population we investigated, QoL in surgically treated patients was better than that in conservatively managed patients.
Keywords: spondylodiskitis; quality of life; surgery; conservative treatment